THE EFFECT OF JOB CHARACTERISTICS AND HR DEVELOPMENT ON EMPLOYEE PERFORMANCE OF FOOD AND BEVERAGES SERVICE DEPARTMENT AT KUTA PARADISO HOTEL BALI - Drevy Dallesandry Malalantang (CV. Adiba Aisha Amira, 2024)
Kuta Paradiso Hotel Bali is a service organization that requires quality human resources. This study used a survey method to observe and examine directly the performance of employees which aimed to describe and explain the relationship between variables and phenomena that occured and were systematically studied on 66 employees. The results of multiple linear regression calculations showed that the characteristics of work and human resource development are Y=19.169+ 0.181X1+ 0.418X2. This means that every increase in one score in the X1 variable on job characteristics will affect the Y variable, with employee performance of 0.181, and an increase in the X2 variable will affect the Y variable by 0.418. Partially based on tcount with the score of tTable that Tcount ≥ Ttable. The scores 2,242>1,997 for the X1 variable, job characteristics affect the Y variable on employee performance. Furthermore, 4.758>1.997 for the X2 variable has an effect on the Y variable, it means that H1 is accepted and H0 is rejected. For multiple tests based on Fcount with FTable score, the results show that Fcount≥FTable for each 20.623>3.14, it means H1 is accepted and H0 is rejected or in other words that job characteristics and HR development simultaneously affect employee performance. The conclusion proves that the proposed hypothesis is proven correct and statistically proven.